As I Remember: John Paul Riebel (1967)
George P. Cooper's interview with John Paul Riebel, a former English Department faculty member at Cal Poly from 1947 to 1967. [00:00:02] As I Remember Opening [00:00:13] Riebel describes how he heard about Cal Poly [00:00:45] Riebel describes how Cal Poly heard about him [00:03:16] Riebel recalls how he got into a minor motorbike accident on his way back to Michigan [00:04:14] Riebel discusses when he arrived at Cal Poly [00:04:52] Riebel discusses his first major assignment as a member of the English Department at Cal Poly [00:05:49] Riebel discusses how often he taught English 100 [00:06:08] Riebel discusses how he got into teaching technical writing, his education background, and his work experience in technical writing [00:09:08] Riebel recalls witnessing time-wasting in industry as a result of ineffective technical writing skills [00:10:49] Riebel discusses his first published book, "How to Write Successful Business Letters in Fifteen Days" [00:13:01] Riebel discusses his other publications [00:14:20] Riebel talks about how he's still actively engaged in writing [00:14:44] Riebel discusses his letter writing clinics he had with various corporations [00:16:16] Riebel discusses how he came up with the title "How to Riebelize Your Writing" [00:17:33] Riebel discusses his public relations involvement at Cal Poly and "selling Cal Poly" [00:19:59] Riebel discusses his reasons for retiring [00:21:24] Riebel discusses his strong support of the "Learn By Doing" philosophy at Cal Poly [00:23:50] Interview wrap-up: Riebel says that he's still a Cal Poly man though he's retiring